Surface Structure of MgO Thin Films Revealed from X-ray Reflectivity and Near-Edge X-ray Absorption Fine Structure Measurements - Singh, Jitendra Pal; Lim, Weon Cheol; Lee, Ik-Jae; Won, Sung Ok; Chae, Keun Hwa (AMER SCIENTIFIC PUBLISHERS, 2018)
In the present work, surface structure of MgO thin film deposited using radio frequency sputtering are discussed. These films were deposited for sputtering durations of 324 and 400 min while maintaining substrate temperature at 300 K and sputtering power at 40 W. The deposited films were further annealed at 300, 500 and 800 degrees C in order to see the effect of annealing on the surface structure. X-ray reflectivity measurements exhibit the improvement of density as well as the modification of surface of MgO thin films with increase of annealing temperature. Nearedge X-ray absorption fine structure measurements reveal that Mg2+ ion coordination is able to sustain high temperature of 800 degrees C without any deformation. Moreover, surface oxygen which adsorb during deposition moves away with the increase of annealing temperature.
Keywords: MULTILAYER; EPITAXY; GROWTH